Depression and oral health-related quality of life: A longitudinal study - Nerobkova, Nataliya; Park, Eun-Cheol; Jang, Sung-In (Frontiers in Public Health, 2023)
Objectives Geriatric oral health-related quality of life is a relatively new but rapidly growing concept as it is directly related to the general wellbeing and self-esteem of older adults. This study assessed the impact of worsening depression symptoms on oral health-related quality of life using representative nationwide data of Korean older adults. Methods This study comprised a longitudinal sample of older adults aged ≥60 from the Korean Longitudinal Study of Aging (2016–2020). After applying the exclusion criteria, 3,286 participants were included in the study. Depression status was determined through the biennial assessment of the short-form Center for Epidemiologic Studies Depression Scale (CESD-10); oral health was measured using the Geriatric Oral Health Assessment Index (GOHAI). We employed the lagged general estimating equations to assess the temporal effect of the CESD-10 score change on the GOHAI score. Results A decrease in CESD-10 score over a 2-year period was significantly associated with a decrease in GOHAI score in men and women: β = −1.810 and β = −1.278, respectively (p-values < 0.0001). Furthermore, compared to the same or improved CESD-10 score, worsening of the score on 1–2 points detected the β = −1.793 in men and β = −1.356 in women, and worsening on ≥3 points: β = −3.614 in men and β = −2.533 in women. Conclusions This study found that depression exacerbation is negatively associated with oral health-related quality of life in later life. Further, a more significant worsening of depression symptoms was correlated with lower scores for oral health-related quality of life in our study population.